From 1a26030f239714f4c3bf3ead418688661d725f61 Mon Sep 17 00:00:00 2001 From: Pietro Monticone <38562595+pitmonticone@users.noreply.github.com> Date: Mon, 15 Apr 2024 15:06:20 +0200 Subject: [PATCH] update --- blueprint/src/chapters/0-introduction.tex | 2 +- blueprint/src/chapters/2-case2.tex | 10 +++++----- 2 files changed, 6 insertions(+), 6 deletions(-) diff --git a/blueprint/src/chapters/0-introduction.tex b/blueprint/src/chapters/0-introduction.tex index 30fb22c..ab75b4c 100644 --- a/blueprint/src/chapters/0-introduction.tex +++ b/blueprint/src/chapters/0-introduction.tex @@ -68,7 +68,7 @@ \chapter{Introduction} Since $\eta$ corresponds to a third root of unity, we have that $\eta^3 = 1$, which implies that $\eta^2 = \eta^{-1}$. Since $\eta$ corresponds to a root of the equation $x^2 + x + 1 = 0$, then $\eta^2 = -1 - \eta$. - Substituting back, we have that $\lambda^2 = (-1 - \eta) - 2\eta + 1 = -3\eta$. + Substituting back, we have that $\lambda^2 = (-1 - \eta) - 2\eta + 1 = s-3\eta$. \end{proof} \begin{theorem} diff --git a/blueprint/src/chapters/2-case2.tex b/blueprint/src/chapters/2-case2.tex index 1859a62..9bfdfdb 100644 --- a/blueprint/src/chapters/2-case2.tex +++ b/blueprint/src/chapters/2-case2.tex @@ -13,7 +13,7 @@ \chapter{Case 2} \end{lemma} \begin{proof} \leanok - Since $3 \divides a^3 + b^3 = c^3$, then $3 \divides c$. \\ + Since $3 \divides a^3 + b^3 = c^3$, then $3 \divides c$. Then $3 \divides gcd(a,b,c)$. \end{proof} @@ -29,7 +29,7 @@ \chapter{Case 2} \end{lemma} \begin{proof} \leanok - Since $3 \divides c^3 - a^3 = b^3$, then $3 \divides b$. \\ + Since $3 \divides c^3 - a^3 = b^3$, then $3 \divides b$. Then $3 \divides gcd(a,b,c)$. \end{proof} @@ -44,7 +44,7 @@ \chapter{Case 2} \end{lemma} \begin{proof} \leanok - Since $3 \divides c^3 - b^3 = a^3$, then $3 \divides a$. \\ + Since $3 \divides c^3 - b^3 = a^3$, then $3 \divides a$. Then $3 \divides gcd(a,b,c)$. \end{proof} @@ -184,10 +184,10 @@ \chapter{Case 2} lmm:lambda_not_dvd_two} Since $\lambda \notdivides a$, then $\lambda^4 \divides a^3 - 1 \lor \lambda^4 \divides a^3 + 1$ by - \Cref{lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd}. \\ + \Cref{lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd}. Since $\lambda \notdivides b$, then $\lambda^4 \divides b^3 - 1 \lor \lambda^4 \divides b^3 + 1$ by - \Cref{lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd}. \\ + \Cref{lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd}. We proceed by analysing each case: \begin{itemize} \item Case $\lambda^4 \divides a^3 - 1 \land \lambda^4 \divides b^3 - 1$.